1986
DOI: 10.1007/bf02347022
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal abundance and vertical distribution of the <3‐μm phytoplakton in the north basin of Lake Biwa

Abstract: The seasonal changes in the size-fractionated chlorophyll a concentrations (<3 I~m, 3 to 25 ~tm, and >25 ~tm) were investigated at a pelagic site of the north basin of Lake Biwa during June to December 1985. Autofluorescing plankton cells in the <3-1am fractions were also examined using the fluorescein isothiocyanate staining epifluorescence microscopic technique. The < 3-~tm phytoplankton (usually dominated by chroococcoid cyanobacteria except for a few cases dominated by small eukaryotes)showed a clearly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
5
34
1
1
Order By: Relevance
“…The percentage contribution of picoplankton to the total biomass in the present study was lower than previous values, but the absolute chlorophyll a concentrations (mg m -3 ) were 3-14 times higher than the maximum value in previous reports . A high value such as that observed in this study has apparently not been reported elsewhere (Nagata, 1986 ;Weisse, 1988) . Weisse (1988) suggested that a positive relationship between the trophic state of waters and picoplankton abundance is likely .…”
Section: Discussionsupporting
confidence: 66%
“…The percentage contribution of picoplankton to the total biomass in the present study was lower than previous values, but the absolute chlorophyll a concentrations (mg m -3 ) were 3-14 times higher than the maximum value in previous reports . A high value such as that observed in this study has apparently not been reported elsewhere (Nagata, 1986 ;Weisse, 1988) . Weisse (1988) suggested that a positive relationship between the trophic state of waters and picoplankton abundance is likely .…”
Section: Discussionsupporting
confidence: 66%
“…5), suggesting that the majority of viruses in both the upper and deeper layers of Lake Biwa are coupled with bacteria. However, temporal resolutions of our data (sampling with a monthly interval) were probably too low to capture temporal dynamics of cyanophages and their hosts (picoplanktonic cyanobacteria display seasonal peaks during warm seasons in Lake Biwa; Nagata 1986, Maeda et al 1992. Thus, we do not exclude the possibility that cyanophages are important components of viral communities in Lake Biwa, as suggested in other lakes (Maranger & Bird 1995, Clasen et al 2008.…”
Section: Discussionmentioning
confidence: 87%
“…In Lake Biwa, however, densities of up to lo6 cells ml-' are considerably higher than in mesotrophic lake in general. Nagata (1986Nagata ( , 1988 reported that in Lake Biwa, the highest cell density of unicellular chroococcoid cyanobacteria (< 3 ym) was 3 x lo5 cells ml-' in late summer 1984 and 1985. Hence, the unusually high abundance up to lo6 cells ml-' should be checked from now on in order to find out whether it is a common phenomenon in this lake.…”
Section: Resultsmentioning
confidence: 99%